Muhammad Shahrur’s Hermeneutics: Interpreting Cultural Phenomena Through a Modern Islamic Lens and Contextual Linguistic Analysis - Fauzi Fauzan El Muhammady (Modern Islamic Studies and Sharia Research, 2025)
In the context of tafsir studies, especially those concerning the language approach has a very significant role. History records that the reading of the Quranic text with a language approach has been done since the time of the Prophet, companions, tabi'in and continues from generation to generation until now. One of the linguistic discourses that became the theme of Muhammad Syahrur's debate was about the synonymity of the Quran. The synonymity of the meaning of a word in any language is a common thing. Likewise, the Quran is inseparable from this element of synonymity, because - even though the Quran as a transcendent revelation of God, has been formed into Arabic text. In understanding the Quran, Muhammad Syahrur tries to study interpretation with theological reconstruction and traditional interpretation. For Muhammad Syahrur, the language of the Quran remains 'tauqifi' even though its content is 'interpretable', and contextualization is in the text itself through linguistic structures. Therefore, Muhammad Syahrur considers that there is no synonymity in language, especially in the Quran. Pendekatan bahasa dalam konteks kajian tafsir memiliki peranan yang sangat signifikan. Sejarah mencatat bahwa pembacaan teks Al Quran dengan pendekatan bahasa telah dilakukan sejak masa Rasulullah, sahabat, tabi’in dan terus berlanjut dari generasi ke generasi hingga sekarang. Salah satu diskursus kebahasaan yang menjadi tema perdebatan Muhammad Syahrur adalah mengenai sinonimitas Al Quran. Sinonimitas makna sebuah kata dalam bahasa manapun merupakan hal yang lazim terjadi. Demikian halnya dengan Al Quran yang tidak terlepas dari unsur sinonimitas ini, sebab - meski Al Quran sebagai wahyu Tuhan yang bersifat transenden, telah terbentuk ke dalam teks berbahasa Arab. Dalam memahami Al Quran Muhammad Syahrur mencoba mengkaji penafasiran dengan rekonstruksi teologi dan penafsiran tradisional. Bagi Muhammad Syahrur bahasa Al Quran tetap ‘tauqifi’ walau dalam kandungannya ‘interpretable’, dan kontekstualisasi ada pada teks itu sendiri melalui struktur linguistik. Karena itu, Muhammad Syahrur menilai bahwa tidak ada sinonimitas dalam bahasa, khususnya pada Al Quran